Quasi-Z-Source Inverter Topologies with Reduced Device Rating: a Review - V. Raghavendra Rajan; Premalatha L. (Institute of Advanced Engineering and Science, 2017)
Quasi-Z-Source Inverter (QZSI) has introduced a new wave of interest in engineering industry and research. Reduction in device rating has been the main objective in introducing QZSI topologies. The introduced topologies in QZSI have proven to be feasible in a wide range for high power with medium voltage applications. This paper mainly focuses on QZSI topologies with continuous input current conduction and also power conditioning in the renewable energy system. Based on a detailed comparison of these topologies suitable QZSI can be arrived for a given application.